2021
DOI: 10.3390/cancers13071486
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Interventions for Women with a BRCA1 or BRCA2 Mutation: A Scoping Review

Abstract: This scoping review aimed to explore the effectiveness of psychological and psychoeducational interventions for BRCA mutation carriers. Four electronic bibliographic databases were searched. After review, 23 articles that described or assessed forms of an additional psychosocial intervention for individuals with a BRCA mutation were identified and included. Intervention types discussed in the articles were telephone-based peer-to-peer counselling (5), online communities (4), in-person group counselling (8), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Anxiety and depression have been known to increase both during and after genetic testing for BRCA1/2 mutations [12][13][14]. For some populations such as Hispanic women, testing positive for BRCA1/2 mutations may feel like a death sentence, because breast cancer is the leading cause of death among this group and increase feelings of hopelessness, stress, and anxiety [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and depression have been known to increase both during and after genetic testing for BRCA1/2 mutations [12][13][14]. For some populations such as Hispanic women, testing positive for BRCA1/2 mutations may feel like a death sentence, because breast cancer is the leading cause of death among this group and increase feelings of hopelessness, stress, and anxiety [52].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse mental health outcomes coexist with the impending risk of breast and ovarian cancers among BRCA1/2positive women in conjunction with associated prophylactic surgeries and ongoing surveillance that are necessary for health maintainence [12][13][14]. The constant worry about affected family members, risk of cancer, future childrearing, among others has a negative effect on mental health [14][15][16], health-related quality of life [17] (especially after prophylactic surgery [18,19]), and perceived health [20,21] among this population.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have assessed psychological wellbeing and morbidity in BRCA1/2 pathogenic variant carriers, both qualitatively [ 19 , 21 , 22 , 23 , 24 ] and quantitatively [ 25 , 26 , 27 ]. Previous reviews have attempted to condense the evidence available [ 12 , 20 , 26 , 28 , 29 , 30 , 31 ]. However, these reviews (1) have focused on the efficacy of psychosocial interventions [ 28 , 29 ], (2) have focused on the psychological effects of different risk-management strategies [ 12 , 31 ], (3) have only included cancer-affected BRCA1/2 carriers [ 30 ], or (4) have reported men and women or cancer-unaffected and cancer-affected BRCA1/2 pathogenic variant carriers combined [ 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a data repository study conducted by Myriad Genetics, BRCA1/2 mutations were found in 14.8%, 15.6%, 12.7%, and 13.2% of tested Hispanic, African, Asian, and Native American women, respectively. Previous literature has focused heavily on the psychosocial impact of receiving a BRCA1/2 diagnosis [21][22][23] and undergoing surgery or surveillance for risk reduction or early detection [24][25][26]. Unfortunately, most of these studies have sampled high-risk English-speaking non-Hispanic white women [22,25,27], such as Ashkenazi Jewish populations [28][29][30], limiting the generalizability that genetic testing and BRCA1/2-related experiences have to racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%